External nasal gland morphology of Eurycea bislineata (Amphibia, Urodela, Plethodontidae). (20th June 2022) - Trame, Samantha D.; Denova, Jacob R.; Pereira, Kenzie E.; McClelland, Sara J.; Gribbins, Kevin M.; Rheubert, Justin L.; Siegel, Dustin S.
Abstract: Plethodontid salamanders possess numerous courtship glands. Previous studies have shown that the glands are more prominent in male individuals than females, and often experience periods of atrophy and hypertrophy throughout the year that correlate to the nonmating and mating seasons, respectively. We sampled male and female Eurycea bislineata throughout the year to test the hypothesis that external nasal glands are courtship glands. External nasal glands are paired, branched tubular glands that extend from excretory ducts dorsal to the nares to terminal secretory units posterior to the eyes. We found that the glands hypertrophy and stain/react more intensely with histochemical procedures during the mating season. Hypertrophy of the glands is more pronounced in males, and seasonal variation in epithelial height of external nasal glands of males is significantly correlated to that of seasonal variation in mental gland epithelial height, a known courtship gland found in males, when compared throughout the year. This correlation was not as strong in females, confirming sexual dimorphism of external nasal glands in terms of seasonal variation. We found no ultrastructural differences between male and female external nasal glands. In all specimens, the glandular tubules were lined by a simple, columnar epithelium that was packed with secretory granules that often obscured other cytoplasmic contents. Abstract : External nasal glands of Eurycea bislineata from specimens in nonmating (top) and mating conditions (bottom) with representative histology of the secretory terminals of the glands anterior and posterior to the orbit.